Prevalence and Outcomes of Pancreatic Enzymes Elevation in Patients With COVID-19: A Meta-Analysis and Systematic Review - You Zhou; You Zhou; You Zhou; Yu-Tong Ge; Yu-Tong Ge; Xiao-Xi Yang; Xiao-Xi Yang; Qian Cai; Yan-Bing Ding; Yan-Bing Ding; Liang-Hao Hu; Guo-Tao Lu; et al. (Frontiers Media S.A., 2022)
Background:Although coronavirus disease 2019 (COVID-19) is considered to be a disease that mainly involves the respiratory system, an increasing number of studies have reported that COVID-19 patients had pancreatic enzymes (PE) elevation and even pancreatic injury. The study aims to determine the prevalence of PE elevation, and the relationship between elevated PE and prognosis in COVID-19 patients.MethodsA comprehensive literature search was conducted according to the PRISMA guideline in PubMed, Embase, Scopus, Web of Science, and Google Scholar for studies reporting PE elevation in patients with COVID-19 from 1st January 2020 to 24th November 2021.ResultsA total of 13 studies (24,353 participants) were included in our review. The pooled prevalence of PE elevation in COVID-19 patients was 24% (18%-31%), the pooled odds ratio (OR) of mortality was 2.5 (1.7-3.6), the pooled OR of ICU admission was 4.4 (2.8-6.8), and the pooled OR of kidney injury, respiratory failure and liver injury were 3.5 (1.6-7.4), 2.0 (0.5-8.7), and 2.3 (1.4-3.9) respectively. In addition, the subgroup analysis revealed that although PE elevated to > 3 × upper normal limit (ULN) was significantly related to the mortality (OR = 4.4, 2.1-9.4), it seemed that mild elevation of PE to 1-3 ULN also had a considerable risk of mortality (OR = 2.3, 1.5-3.5).ConclusionsPE elevation was a common phenomenon in patients with COVID-19, and was associated with poor clinical outcomes. However, due to the limited numbers of included studies, the result of our study still needed to be validated.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=295630, identifier: CRD42021295630.